One Village, Three Houses of Worship: Exploring the Dynamics of Religious Tolerance in Indonesia - Maryono, Maryono; Nur Anna, Dian; Musthofa, Muhammad Wakhid (Jurnal Sosiologi Reflektif, 2024)
Indonesia has a long history of religious tolerance, yet the recent increase in incidents of intolerance reflects that this value requires renewed attention from scholars. This study aims to explore how the people of Sayidan interpret and practice tolerance in their daily lives, examining the mechanisms and social structures that have allowed this harmony to persist. Understanding how tolerance is embedded in the life of the Sayidan community is crucial for uncovering broader strategies to sustain religious tolerance in Indonesia.This research employs a phenomenological approach to uncover the meaning and structure of lived experiences related to religious tolerance. The Interpretative Phenomenological Analysis (IPA) method was applied to analyze data gathered from interviews with community leaders, RT/RW heads, religious figures, and youth representatives. The analysis involved several stages, including data familiarization, initial coding, theme development, and interpretative analysis. The findings reveal that tolerance in Sayidan is shaped by strong social and religious elements, further reinforced by economic interactions and a shared political struggle. While the study is limited in terms of generalizing to other contexts, the insights from Sayidan offer important lessons on how religious harmony can be maintained. Indonesia memiliki sejarah panjang toleransi beragama, peningkatan insiden intoleransi dalam beberapa tahun terakhir merefleksikan bahwa hal ini perlu mendapatkan perhatian dari akademisi. Penelitian ini bertujuan untuk mengeksplorasi bagaimana masyarakat Sayidan menafsirkan dan mempraktikkan toleransi dalam kehidupan sehari-hari, dengan menelaah mekanisme dan struktur sosial yang memungkinkan kerukunan tersebut bertahan. Memahami bagaimana toleransi tertanam dalam kehidupan komunitas Sayidan penting untuk mengungkap strategi yang lebih luas dalam mempertahankan toleransi beragama di Indonesia. Penelitian ini menggunakan metode fenomenologis untuk mengungkap makna dan struktur pengalaman hidup yang terkait dengan toleransi beragama. Metode Interpretative Phenomenological Analysis (IPA) diterapkan untuk menganalisis data yang diperoleh dari wawancara dengan tokoh masyarakat, kepala RT/RW, pemimpin agama, dan perwakilan pemuda. Analisis dilakukan melalui tahapan pengenalan data, pengkodean awal, pengembangan tema, dan analisis interpretatif. Hasil penelitian menunjukkan bahwa toleransi di Sayidan terbentuk melalui elemen-elemen sosial dan agama, serta didukung oleh interaksi ekonomi dan perjuangan politik bersama. Meskipun studi ini memiliki keterbatasan dalam hal generalisasi ke konteks lain, temuan dari Sayidan memberikan wawasan penting tentang bagaimana kerukunan beragama dapat dipertahankan.